The effects of legal versus business education on decision making in public administrations with a Weberian tradition - Tim Rosengart; Bernhard Hirsch; Christian Nitzl (Business Research, 2019)
We analyse the socialization effects of a university education on decision making in a public-sector context with a Weberian tradition. The results of our vignette study of 331 law and business students and 155 professionals in German public administrations show that business students-in contrast to law students-make decisions significantly more in line with private-sector logic. This phenomenon is not observed for professionals. Individuals' transformations from student to professional status appear to be affected by particularly strong internal and external pressures to socialize, which widely neutralizes the differences between legal and business professionals.
Keywords: 650; University education; Socialization; Public administration; Weberian tradition; Decision making